49‐4: Late‐News Paper: Intermediate Screen Considered Negative Impact by Ambient Light for Augmented Reality Head‐Up Display Systems. Issue 1 (29th May 2019) - Nagasawa, Atsushi; Watanabe, Junji; Uchida, Atsushi; Takahashi, Tomohiro; Karai, Masaru; Kasai, Hideto
Abstract : KURARAY proposes intermediate screen composed of microlens array for augmented reality head‐up display. The microlens array screen which has accurate mirror matrix enables to reduce negative impact by ambient light. KURARAY's screen will bring safer and more comfortable drive to all automotive drivers near future.